Fragmented QRS complexes are associated with left ventricular dysfunction in patients with type-2 diabetes mellitus: a two-dimensional speckle tracking echocardiography study. Issue 5 (3rd September 2018) - Bayramoğlu, Adil; Taşolar, Hakan; Kaya, Yasemin; Bektaş, Osman; Kaya, Ahmet; Yaman, Mehmet; Günaydın, Zeki Yüksel
Abstract: Background: Heart failure may develop independently of coronary artery disease in diabetes mellitus (DM) patients. Fragmented QRS (fQRS) is a marker of myocardial fibrosis or scar tissue and is related to an increase in cardiovascular adverse events. In this study, we examined the utility of speckle tracking echocardiography (STE) in assessing LV function in DM patients with fQRS. Methods and Results: The current study included 178 consecutive patients diagnosed with type-2 DM. The patients included were separated into two groups: those with ( n  = 50) and without ( n  = 128) fQRS. The two groups were compared by obtaining LV strain values with STE. Statistically significant differences were also identified between fQRS(−) and fQRS (+) groups with respect to Lv-GLS ( p  < .001), maxLAVI ( p  = .020), minLAVI ( p  < .001), E velocity ( p  < .001), E m velocity (0.002), E /Em ratio (<0.001) SRe ( p  < .001), SRe/SRa ratio ( p  < .001), SRivr ( p  < .001) and E /SRivr ratio ( p  < .001). In the multiple linear regression analysis, fQRS ( β  = −2.077, p  = .002) and DM duration ( β  = −0.216, p  = .021) were identified as independent predictors of Lv-GLS. However, fQRS ( β  = 4.557, p  = .001) and minLAVI ( β  = −2.198, p  = .031) were also found to be independent predictors of E /SRivr. We also performed multiple logistic regression analysis and identified Lv-GLS ( β  = −0.557, p  = .001), minLAVI ( β  = −0.769, p  = .001), E / E m ratio ( β  = 0.650, p  = .001) and E /SRivr ( β  = 0.105, p  = .001) as independent predictors of fQRS. Conclusıons: The results of this study revealed that subclinical LV dysfunction was more common in diabetic patients with fQRS. Therefore, determination of fQRS could be an indicator of the diabetic CMP in patients with DM.